Antagonist Test of Streptomyces spp. from Shallot Fields in Bojonegoro Against Fusarium sp. Which Causes Moler Disease In vitro - Hidayati, Kiki; Mujoko, Tri; Wuryandari, Yenny (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Background: Shallots are a horticultural product widely consumed in Indonesia. In 2021, shallot production will decline. This is due to pest and disease attacks on plants. Fusarium sp. is a pathogen that causes the primary disease in shallots, namely moler disease, which can cause losses of up to 50%, so control activities must be carried out. This research aims to determine the potential of Streptomyces sp. bacteria from exploring shallot planting areas in Bojonegoro against Fusarium sp. fungi in vitro. Methods: This study used 15 isolates of Streptomyces sp. from exploration results tested with Fusarium sp. using the dual culture method, and negative control (only Fusarium sp.) repeated 3 times for each treatment. Observations were carried out every day for 7 days by observing the growth of Fusarium sp. hyphae and their inhibitory power. Result: The research showed that isolate S8 had the highest inhibitory power, 49.5%. Meanwhile, the one with the lowest results was isolated S1, 34.5%. From the chitinase test results, the chitinocytic index of isolate S8 was 5.2, which is in the high category. Meanwhile, the isolate S8 cellulolytic index was 4.8 and was classified as high. Conclusions: All Streptomyces sp.p isolates inhibited the growth of Fusarium sp., which was characterized by an inhibition zone compared to the control treatment.